Variation in mental health-related sickness absence duration: The role of occupational health professionals - Sheila Timp; Nicky van Foreest; Willem van Rhenen (PLoS ONE, 2026)
Mental health-related disorders are prevalent among the working population and account for a large proportion of sickness absence. Occupational health professionals (OHPs) play a key role in supporting employee recovery and reintegration, yet little is known about the extent to which individual OHPs affect return-to-work outcomes. Previous studies suggest that OHPs might influence absence duration, but comprehensive quantitative analyses examining variation between OHPs are lacking. In this study, we determine the variation in sickness absence duration attributable to OHPs in mental health-related cases. We analyze a large dataset of more than 30,000 sickness absence cases involving employees diagnosed with mental health-related disorders across multiple sectors. A cross-classified multilevel model was applied to estimate variance attributable to OHPs while controlling for other sources of variation. Our results show substantial variation in mental health-related sickness absence duration between OHPs ( σ 2 = 0.13 ). This corresponds to marked differences in return-to-work outcomes: for high-performing OHPs, the median absence duration is 18 weeks or less, whereas for low-performing OHPs, the median duration is 28 weeks or more. Individual, organizational, and sectoral factors also contribute considerably to differences in sickness absence duration. Including OHP- and organization-level random effects reduced the estimated individual-level variance by about 50%, indicating that differences across providers and employers are relevant in reducing sickness absence duration. Based on this, we argue that OHPs and organizations should work in concert to reduce sickness absence durations. Future research should identify which specific OHP characteristics and practices are most helpful in accomplishing this.